2015
DOI: 10.1038/npp.2015.221
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Regulation of GABAergic Neurons Within the Ventral Tegmental Area During Withdrawal from Chronic Morphine

Abstract: Opioid dependence is accompanied by neuroplastic changes in reward circuitry leading to a negative affective state contributing to addictive behaviors and risk of relapse. The current study presents a neuroimmune mechanism through which chronic opioids disrupt the ventral tegmental area (VTA) dopaminergic circuitry that contributes to impaired reward behavior. Opioid dependence was induced in rodents by treatment with escalating doses of morphine. Microglial activation was observed in the VTA following spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 58 publications
4
87
2
Order By: Relevance
“…In contrast, the ratio of phosphorylated-S940 KCC2 to total KCC2 protein after stress was significantly lower compared to control (Figure 7F, G): 78.3 ± 5.5% for monomer, 79.6 ± 4.7% for dimer. Importantly, as also reported previously (Taylor et al, 2015), immunolabeling analysis in the VTA suggested that KCC2 protein was expressed exclusively on non-DA neurons (data not shown), which is consistent with the presence of another chloride extrusion mechanism in DA neurons (Gulacsi et al, 2003). …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the ratio of phosphorylated-S940 KCC2 to total KCC2 protein after stress was significantly lower compared to control (Figure 7F, G): 78.3 ± 5.5% for monomer, 79.6 ± 4.7% for dimer. Importantly, as also reported previously (Taylor et al, 2015), immunolabeling analysis in the VTA suggested that KCC2 protein was expressed exclusively on non-DA neurons (data not shown), which is consistent with the presence of another chloride extrusion mechanism in DA neurons (Gulacsi et al, 2003). …”
Section: Resultssupporting
confidence: 90%
“…These findings highlight the importance of glucocorticoid signaling within the VTA, but we do not rule out the participation of other stress signaling molecules or hormones, such as CRF, in mediating stress-induced adaptations (Hwa et al, 2016; Ungless et al, 2003). Furthermore, the effect of glucocorticoids on VTA GABA neurons may involve the activity of noradrenaline, glutamate, and glial cells (Coull et al, 2003; Hewitt et al, 2009; Lee et al, 2011; Taylor et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Figures were prepared digitally using Adobe Photoshop CS5.1 and Adobe Illustrator CS5.1 (Adobe Systems In., San Jose, CA). To compare the expression differences between yolk sac and labyrinth, fluorescent intensities from Maoa , Tph1 , or Ddc were quantified using FIJI ImageJ software (NIH) [30]. The mean intensities from 3 random areas of the same size (45.19 μm x 34.92 μm) in the labyrinth or yolk sac were measured for each probe.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, brain regions associated with reward and affective behaviors have also been implicated [13]. It has been shown that chronic opioid administration in rodents promoted GABA-mediated excitation [14] and loss of neuronal inhibition via reduction of KCC 2 currents in the ventral tegmental area [15]. Furthermore, acute morphine withdrawal in rats increased c-Fos expression in dopaminergic neurons within nucleus accumbens shell in mice [16], and phosphorylation of NMDARs in the accumbens [17].…”
Section: Central Mechanisms Of Opioid Withdrawalmentioning
confidence: 99%